KÖPECZI – KIRKÓSA JÚLIA ECATERINA, “The Aesthetics of the Verdian Opera Reflected in its Female Characters. Between Lyric and Dramatic”, Ed. MediaMusica, Cluj-Napoca, 2010. - MIKLÓS BOGNÁR, Noémi (Studia Universitatis Babes-Bolyai Musica, 2010)
The book mentioned in the title written by Köpeczi – Kirkósa Júlia Ecaterina is divided into four volumes, each containing important information regarding the esthetical approach and the interpretation of the female characters created by Verdi. The four volumes are structured as follows: The message of the Verdian dramaturgy within the field of romantic aesthetics. The aspects of the belcanto style in the light of Verdian music. The stylistic-aesthetic features of the Verdian creation in the light of some of the paradigmatic female roles I. The stylistic-aesthetic features of the Verdian creation in the light of some of the paradigmatic female roles II.